Human Factors In Consumer Products. - Stanton, Neville A. (Neville Anthony), 1960- (Taylor & Francis, 1997)
The design of consumer products has a central role in its potential for contributing to a healthier living and working space. However, too often consumers are only aware of the designers' role when bad practice manifestly exacerbates the easy application of basic functionality. This important book places human factors perspective firmly at the centre of good practice in consumer product design, encouraging rigorous human factors evaluation and methodology as an essential component of the design process.